A. \(a + b = 6\)
B. \(a + b = 11\)
C. \(a + b = 4\)
D. \(a + b = 8\)
A
Đặt \({\log _9}x = t\)
Theo đề ra ta có \(\left\{ \begin{array}{l}{\log _9}x = {\log _6}y = t\\{\log _9}x = {\log _4}\left( {x + y} \right) = t\end{array} \right. \Rightarrow \left\{ \begin{array}{l}x = {9^t} & & \left( 1 \right)\\y' = {6^t} & & \left( 2 \right)\\x + y = {4^t} & \left( 3 \right)\\\frac{x}{y} = {\left( {\frac{3}{2}} \right)^t} & \left( 4 \right)\end{array} \right.\)
Từ (1), (2) và (3) ta có \({9^t} + {6^t} = {4^t} \Leftrightarrow {\left( {{3^t}} \right)^2} + {\left( {3.2} \right)^t} - {4^t} = 0 \Leftrightarrow {\left( {\frac{3}{2}} \right)^{2t}} + {\left( {\frac{3}{2}} \right)^t} - 1 = 0\)
\( \Leftrightarrow \left[ \begin{array}{l}{\left( {\frac{3}{2}} \right)^t} = - \frac{{ - 1 + \sqrt 5 }}{2}\left( {TM} \right)\\{\left( {\frac{3}{2}} \right)^t} = \frac{{ - 1 - \sqrt 5 }}{2}\left( L \right)\end{array} \right.\)
Thế vào (4) ta được \(\frac{x}{y} = {\left( {\frac{3}{2}} \right)^t} = \frac{{ - 1 + \sqrt 5 }}{2} = \frac{{ - a + \sqrt b }}{2} \Rightarrow a = 1;\,\,b = 5\)
Câu hỏi trên thuộc đề trắc nghiệm dưới đây !
Copyright © 2021 HOCTAP247